INOVASI GAMIFIKASI WEBSITE PERSY PERFUME SEBAGAI PENGALAMAN KONSUMEN DALAM PEMILIHAN PARFUM KEPRIBADIAN SECARA DIGITAL - Pradika, Mohammad Fawaid; Alamiyah, Syifa Syarifah (ANALISIS, 2024)
This research will discuss how the gamification innovation of the Persy Perfume website in providing a consumer experience for digital personality perfume selection. The trend of using perfume products in Indonesia is increasing, marked by the emergence of many local perfume brands with globally competitive quality. However, product innovation is needed to increase consumer interest in using the product, one of the strategies that can be used is to provide a consumer experience in purchasing products. Persy Perfume is a local brand that uses the aroma of Indonesian spices as a unique selling product and elevates the local culture of wayang as a variant of each scent. Persy through its website provides a consumer experience through "Petualangan Persy Aroma" as a form of innovation in the form of personality test gamification to provide perfume scent recommendations that match the consumer's personality in digital purchases. This research is research with a qualitative descriptive method, to find out how gamification innovations in providing consumer experience to increase consumer interest in shopping for perfume digitally. The result found is that Persy Perfume has found a new innovation in providing a consumer experience through the " Petualangan Persy Aroma", this is an interesting innovation and a new way in the perfume industry to provide a digital consumer experience. By providing a new experience for consumers, this can invite interest from potential consumers to buy the product.